Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Papan Hitung untuk Meningkatkan Hasil Belajar Matematika Penjumlahan dan Pengurangan Siswa Kelas IA SD Negeri Purwoyoso 04 - Sutta, Sindiyantika; Dlorifah Fithriana, Sely; Ayu Nur Octaviany, Niken; Citra Pratiwi, Delia (Papanda Publisher, 2024)
The aim of this research is to determine the effectiveness of implementing the Problem-Based Learning (PBL) learning model assisted by calculating board media to improve the learning outcomes of class IA students at SD Negeri Purwoyoso 04 in mathematics learning about addition and subtraction. The method used in this research is descriptive qualitative with a case study approach. The data used in this research are the results of working on LKPD and the results of working on evaluation questions. As a result of working on the LKPD, almost all students have understood the problems in the LKPD regarding addition and subtraction, although some students are still confused this does not become an obstacle in the learning process because they can discuss with the group and the teacher can guide them. Therefore, the application of the Problem-Based Learning (PBL) Learning Model assisted by calculating board media is effective in improving student learning outcomes in mathematics learning about addition and subtraction.